Adverse Childhood Experiences, Early and Nonmarital Fertility, and Women's Health at Midlife. (September 2019) - Williams, Kristi; Finch, Brian Karl
Adverse childhood experiences (ACEs) have powerful consequences for health and well-being throughout the life course. We draw on evidence that exposure to ACEs shapes developmental processes central to emotional regulation, impulsivity, and the formation of secure intimate ties to posit that ACEs shape the timing and context of childbearing, which in turn partially mediate the well-established effect of ACEs on women's later-life health. Analysis of 25 years of nationally representative panel data from the National Longitudinal Study of Youth (NLSY79; n = 3, 893) indicates that adverse childhood experiences predict earlier age at first birth and greater odds of having a nonmarital first birth. Age and marital status at first birth partially mediate the effect of ACEs on women's health at midlife. Implications for public health and family policy aimed at improving maternal and child well-being are discussed.